ANALISIS PENGARUH PERSEPSI HARGA, PROMOSI, DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN COCA-COLA DI KECAMATAN SEMARANG SELATAN - Puspitayani, Intan Margiyawati; Yuniawan, Ahyar (Diponegoro Journal of Management, 2015)
This study aims to analyze Â the influence of price perception, promotion, and distribution to the purchase decision of Coca-Cola. Where the independent variables are price perception, promotion, and distribution affect the purchase decision as the dependent variable. The data in this study were collected through questionnaires and implemented to 100 consumer ofÂ  Coca-Cola as the study sample. Data analysis methods used are quantitative analyzes, the test reliability and validity, the classical assumption test, t test and F test, coefficient of determination as well as multiple linear regression analysis. Based on the results of data analysis, showed that: price perception have positive and significant impact as well as having the greatest influence on purchase decisions, promotion have positive and significant influence on purchase decisions, distribution have a positive and significant influence on purchase decisions. The results of analysis using the coefficient of determination is known that 33,4% variable purchase decision can be explained by variations of the variables price perception, promotion, and distribution, while 66,6% explained by other variables that are not included in this study.